The use of cerebral computed tomographic angiography as an ancillary investigation to support a clinical diagnosis of death using neurological criteria: a consensus guideline. (29th January 2023) - Thomas, E. O.; Manara, A.; Dineen, R. A.; Mortimer, A.; Aziz, O.; Dean, P.; Elliott, P.; Summers, D. M.; Whitfield, P. C.; Hutchinson, P. J.; Gardiner, D.
Summary: This multidisciplinary consensus statement was produced following a recommendation by the Faculty of Intensive Care Medicine to develop a UK guideline for ancillary investigation, when one is required, to support the diagnosis of death using neurological criteria. A multidisciplinary panel reviewed the literature and UK practice in the diagnosis of death using neurological criteria and recommended cerebral CT angiography as the ancillary investigation of choice when death cannot be confirmed by clinical criteria alone. Cerebral CT angiography has been shown to have 100% specificity in supporting a diagnosis of death using neurological criteria and is an investigation available in all acute hospitals in the UK. A standardised technique for performing the investigation is described alongside a reporting template. The panel were unable to make recommendations for ancillary testing in children or patients receiving extracorporeal membrane oxygenation.